Prevalencia de la hiperplasia epitelial focal en pacientes atendidos en el servicio de dermatología del HRDT 1998 - 2014 - Llanos Vera, Carlos Enrique (2015)
The aim of this study is to determine the prevalence of focal epithelial hyperplasia (FEH) or Heck's disease in patients attending in the dermatology service of Hospital Regional Docente de Trujillo (HRDT) during the period January 1998 - December 2014. The method of study is descriptive, cross-sectional and retrospective that included a review of 127 medical records diagnosed with Focal Epithelial Hyperplasia. Whose results reported a prevalence of 0.17 % of FEH a total of 74640 patients treated, being the age group between 0-20 years of age the most affected (86%) and equally affecting both genders getting the female 51 %. The main place of origin was Trujillo with 52 cases and anatomical regions most affected by this disease were, in descending order: mucosa of the upper and lower lip (33%), buccal mucosa - upper and lower lip (20%), labial mucosa lower (16%) and buccal mucosa (10%). We conclude that the prevalence of focal epithelial hyperplasia in patients attending in the dermatology service Hospital Regional Docente de Trujillo is 0.17%, pathology rare in the population studied